2005
DOI: 10.1111/j.1525-1497.2005.0180.x
|View full text |Cite
|
Sign up to set email alerts
|

What can hospitalized patients tell us about adverse events? Learning from patient-reported incidents

Abstract: Purpose: Little is known about how well hospitalized patients can identify errors or injuries in their care. Accordingly, the purpose of this study was to elicit incident reports from hospital inpatients in order to identify and characterize adverse events and near‐miss errors. Subjects: We conducted a prospective cohort study of 228 adult inpatients on a medicine unit of a Boston teaching hospital. Methods: Investigators reviewed medical records and interviewed patients during the hospitalization and by te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
285
1
13

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(308 citation statements)
references
References 29 publications
9
285
1
13
Order By: Relevance
“…individual interviewing of hospitalised patients or conducting follow-up by telephone on patient experiences of using health services) can be most effective in increasing the amount of patient feedback [37]. Other studies have also shown the effectiveness of actively solicited patient feedback [37,62]. …”
Section: Resultsmentioning
confidence: 99%
“…individual interviewing of hospitalised patients or conducting follow-up by telephone on patient experiences of using health services) can be most effective in increasing the amount of patient feedback [37]. Other studies have also shown the effectiveness of actively solicited patient feedback [37,62]. …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the risks of these handoffs may be underestimated, since prior studies show that patients are often able to report adverse events that would be missed by chart review. 14,15 Furthermore, patients may be aware of the quality of inter-physician communication during care transitions and may give additional insights into methods to improve communication during clinic handoffs. 16 Therefore, to improve clinic handoffs, more insight into patient experiences and patient needs during this transition are crucial.…”
Section: Introductionmentioning
confidence: 99%
“…6,[11][12][13] The discussion highlights a patient safety perspective brought forth by the mother and allows for dialogue concerning existing communication and supervision barriers in the delivery of safe patient care and thoughts on improvement strategies. [14][15][16] Much of medical training is focused on the acquisition of knowledge and skills; however, it is the affective domain of learning that is responsible for changing behaviors.…”
Section: Discussionmentioning
confidence: 99%